Rochester Youth Development Study Phase 1 Data, 1988-1992 (Rochester, New York) - Thornberry, Terence P. ([Verlag nicht ermittelbar], 2016)
The Rochester Youth Development Study (RYDS) is part of the larger "Program of Research on the Causes and Correlates of Delinquency" initiated by the Office of Juvenile Justice and Delinquency Prevention in 1986. The RYDS examines causes and consequences of delinquency and drug use in an urban sample of adolescents. A sample of 1,000 seventh and eighth grade students was selected from Rochester, New York, public schools during the 1987-1988 academic year. These students were selected to over-represent youth at high risk for serious delinquency and drug use. In Phase 1 each student was interviewed nine times at six-month intervals from the Spring of 1988 until the Spring of 1992. In addition, interviews with one primary caretaker of each student were conducted eight times at six-month intervals from the Spring of 1988 until the Fall of 1991. The interviews lasted about an hour and cover a wide range of topics including social class position, family structure and processes, educational success, peer relationships, neighborhood characteristics, psychological functioning, social networks, and social support systems, and involvement in prosocial and antisocial behaviors. When appropriate, the research team collected similar information from both the students and parents to provide multiple perspectives on these developmental issues. The research team also collected extensive information about problem behaviors including self-reported delinquency and drug use, gang membership, gun ownership, problem drug use, teenage parenthood, school dropout, and other problem behaviors.